Pengembangan Karier bagi Aparatur Sipil Negara dan Peningkatan Kualifikasi Pegawai pada Kecamatan Ngajum Kabupaten Malang - Hanafiah, Ali; Kumalasari, Klara (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Career development and improving employee qualifications are important elements in forming a professional, competent State Civil Apparatus (ASN) that is able to provide optimal public services. This community service activity aims to improve the understanding and capacity of ASN in the sub-district office environment in planning career paths and encouraging improved qualifications through education, training, and competency development. The activity was carried out in the form of socialization. The results of the activity showed that the participants had a better understanding of career development, as well as the importance of improving qualifications in supporting work effectiveness. In addition, participants showed high enthusiasm for participating in the ongoing self-development program. This activity is expected to be the first step in creating an adaptive, productive, and performance-oriented work culture in the sub-district bureaucratic environment.